Cage effect in the dissociation of van der Waals complexes RgI2 (Rg=Ar, Kr, Xe): A quasiclassical trajectory study - Ibrahim Ali , Noorbatcha (American Institute of Physics (AIP), 1984)
The dissociation dynamics of the RgI2 (Rg=Ar,Kr,Xe) van der Waals complexes have been studied using three‐dimensional quasiclassical trajectories. Specifically, the unimolecular dissociation of RgI2(B  3π) with initial I2 vibrational excitation above the Rg+I+I dissociation limit of the B  3π state was studied. In addition to complete dissociation to atoms, iodine ‘‘recombination’’ was observed to be a major reaction channel. This result is interpreted as a cage‐like effect due to the inert gas atom, which also carries away a large fraction of the energy when the complex dissociates to form I2. The reaction mechanism leading to the formation of molecular products has been found to involve both direct and long‐lived, complex trajectories. Dissociation of the complex RgI2 is favored by near collinear orientations. The decomposition kinetics of the complex are found to be complex and non‐RRKM in character. A four‐step reaction mechanism involving an explicit intramolecular energy transfer step is proposed to explain the calculated time dependence of the product concentrations. The calculated product vibrational distributions are in qualitative agreement with the experimental results.